Profiling the Expression of Endoplasmic Reticulum Stress Associated Heat Shock Proteins in Animal Epilepsy Models. (1st March 2020) - Nowakowska, Marta; Gualtieri, Fabio; von Rüden, Eva-Lotta; Hansmann, Florian; Baumgärtner, Wolfgang; Tipold, Andrea; Potschka, Heidrun
Highlights: Expression of HSPA5 and HSPH4 is altered in rat hippocampus and piriform cortex. The expression rates of HSPA5 and HSPH4 increase with time. HSPA5 and HSPH4 are expressed in neurons; HSPA5 localizes in single astrocytes. In canine patients with structural epilepsy, HSPH4 is up-regulated in CA1 region. HSPA5 and HSPH4 may represent targets for anti-epileptogenic therapies. Abstract: Unfolded protein response is a signaling cascade triggered by misfolded proteins in the endoplasmic reticulum. Heat shock protein H4 (HSPH4) and A5 (HSPA5) are two chaperoning proteins present within the organelle, which target misfolded peptides during prolonged stress conditions. Epileptogenic insults and epileptic seizures are a notable source of stress on cells. To investigate whether they influence expression of these chaperones, we performed immunohistochemical stainings in brains from rats that experienced a status epilepticus (SE) as a trigger of epileptogenesis and from canine epilepsy patients. Quantification of HSPA5 and HSPH4 revealed alterations in hippocampus and parahippocampal cortex. In rats, SE induced up-regulation of HSPA5 in the piriform cortex and down-regulation of HSPA5 and HSPH4 in the hippocampus. Regionally restricted increases in expression of the two proteins has been observed in the chronic phase with spontaneous recurrent seizures. Confocal microscopy revealed a predominant expression of both proteins in neurons, no expression in microglia and circumscribed expression in astroglia. In canine patients, only up-regulation of HSPH4 expression was observed in Cornu Ammonis 1 region in animals diagnosed with structural epilepsy. This characterization of HSPA5 and HSPH4 expression provided extensive information regarding spatial and temporal alterations of the two proteins during SE-induced epileptogenesis and following epilepsy manifestations. Up-regulation of both proteins implies stress exerted on ER during these disease phases. Taken together suggest a differential impact of epileptogenesis on HSPA5 and HSPH4 expression and indicate them as a possible target for pharmacological modulation of unfolded protein response.